Teacher Literacy and Numeracy Skills: International Evidence from PIAAC and ALL - Bart H.H. Golsteyn; Stan Vermeulen; Inge de Wolf (Institute for the Study of Labor (IZA), 2016)
Using the OECD-studies PIAAC and ALL, this paper shows that teachers on average have better literacy and numeracy skills than other respondents in almost all of the 15 countries in the samples. In most countries, teachers outperform others in the bottom percentiles, while in some countries they perform better than others throughout the skill distribution. These results imply that the scope to improve teachers' skills varies between countries and that policy makers should take the shape of the skills distribution into account when designing interventions in order to most efficiently raise teachers' skills.
Keywords: I2; J2; J45; 330; teachers; skills; human capital